If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7b + -6) = 110 Reorder the terms: 5(-6 + 7b) = 110 (-6 * 5 + 7b * 5) = 110 (-30 + 35b) = 110 Solving -30 + 35b = 110 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 35b = 110 + 30 Combine like terms: -30 + 30 = 0 0 + 35b = 110 + 30 35b = 110 + 30 Combine like terms: 110 + 30 = 140 35b = 140 Divide each side by '35'. b = 4 Simplifying b = 4
| -2(5s-6)-12=-2(9s+4)-3 | | 36/2x=6 | | -1.3+2.7=.2y | | -13x+22=37 | | 7/3a=14 | | y=-9x+44 | | 3x(12-3)=27 | | 6x+19=8x+7 | | -2(5x-6)-12=-2(9s+4)-3 | | b+b2+b/6=190 | | 4*x^3+5*x^2+x=1 | | -10m-4=4-10m | | (4+8x)/(2x+1) | | 180=6000*.12*t | | 4(5x-1)-4=14x-2 | | 5(3x+1)=2(5x-4)+6x | | 27(1.4+1.2)-26(1.4+1.2)= | | -65.375=7.2(9c+1) | | (2x+9)+(2x+8)+(2x)=(2x)+(3x+1) | | 2a/3+1/5 | | 7/3x+9/6x=36/9 | | 10y=12.6 | | -3a+4=-8 | | 6(3x-2)=18x-12 | | 4x^2+19x+22=0 | | 35=45 | | (-2/7)(2m+6)=(1/28)m-11 | | x+15+2x=-5-2x-30 | | -14-4(x)=-58 | | 6(2x+6)= | | 8y+3(y-5)=6(y+1)-3 | | 40/x-40x+39=0 |